Reciprocal Regulation of Mitochondrial Fission and Fusion. Issue 7 (July 2020) - Sabouny, Rasha; Shutt, Timothy E.
Abstract : The dynamic processes of mitochondrial fission and fusion are tightly regulated, determine mitochondrial shape, and influence mitochondrial functions. For example, fission and fusion mediate energy output, production of reactive oxygen species (ROS), and mitochondrial quality control. As our understanding of the molecular machinery and mechanisms regulating dynamic changes in the mitochondrial network continues to grow, we are beginning to unravel important signaling pathways that integrate physiological cues to modulate mitochondrial morphology and function. Here, we highlight reciprocal regulation of mitochondrial fusion and fission as an emerging trend in the regulation of mitochondrial function. Highlights: Mitochondria are dynamic organelles constantly undergoing fusion and fission events. The morphology of the mitochondrial network is determined by the balance between fusion and fission events. Changes in mitochondrial morphology facilitate the integration of mitochondrial function with physiological changes in the cell. Hyperfused mitochondrial networks can be due to increased fusion and/or decreased fission. Fragmented mitochondrial networks can be a result of either more fission and/or reduced fusion. An emerging trend in mitochondrial network remodeling is the reciprocal regulation of fission and fusion, where regulatory pathways influence both processes.